Pill popping problems: The non-medical use of stimulant medications in an undergraduate sample. (June 2014) - Gallucci, Andrew R.; Usdan, Stuart L.; Martin, Ryan J.; Bolland, Kathleen A.
<x xml:space="preserve">Abstract</x> Aims: The non-medical use of prescription stimulants (NMUPS) is an emergent health behaviour among undergraduate college students. This study examined the prevalence, primary motivations and risk factors associated with lifetime and current NMUPS among undergraduates. Methods: An anonymous survey examining the NMUPS behaviour was administered in-class to a sample of 1020 of traditional undergraduate university students. Findings: Findings indicated that 35% of students used a prescription stimulant at least once non-medically during their lifetime and 12% had done so in the previous 30 days. Results also indicated that the majority of current and lifetime non-medical users were motivated to engage in the behaviour to improve or enhance academic performance. Further, multivariate logistic regression analyses revealed that students who engaged in current or lifetime NMUPS were more likely to be non-freshmen, affiliated with a Greek organization and diagnosed with attention deficit/hyperactivity disorder (ADHD). Conclusions: Efforts to reduce college students from engaging in NMUPS would benefit by targeting specific portions of the student body. These initiatives should include information about how to address academic problems without abusing stimulant medications.